Sistem Pendukung Keputusan Pemilihan Makanan Balita Menggunakan Metode Weighted Product Berbasis Android - Mufreni, Sadr Lufti; Arizona Firdonsyah; Sabrina Khusnul Khotimah (Computer Science and Information Technology, 2024)
Parents often find it challenging to choose the right foods that meet their toddlers' nutritional needs. Nutritional requirements are crucial during the growth and development phase of toddlers. Ensuring toddlers get proper nutrition is vital for their growth. Selecting the wrong foods can lead to insufficient nutrition, which could hinder their growth and development. This research aimed to develop an Android-based decision support system for selecting toddler foods and making it easier for parents to choose the right foods for their toddlers. This research employed the Weighted Product method, based on six criteria: carbohydrates, protein, fat, vitamin A, iron, and zinc. The data were collected by reviewing literature, conducting field studies, and using the System Development Life Cycle (SDLC) waterfall model for system development. The results rank forty different types of food, with fried shrimp being the top-ranked option. The accuracy of the Weighted Product method is calculated to be 100%.